Rancang Bangun Sistem Informasi Ketersediaan Lokasi Parkir Sepeda Motor (Studi Kasus Institut Informatika dan Bisnis Darmajaya) - Novi Herawadi Sudibyo; Bayu Nugroho; Ikhsan Koirul Bastari (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2020)
Institute of Informatics and Business Darmajaya provides 4 locations to accommodate parking for motorcycles and 3-point car from the parking area that has been provided has not been able menmpang caused the overall vehicle parking arrangements are not good and are still manual. The lack of information about the state of the parking location is also the cause of the irregular and less extensive parking location. By utilizing RFID technology, Arduino, IR sensors, and Led Matrix is expected to be the solution of the problem. detecting when the RFID tag read ID (RFID card) LED matrix displays information on the location of the parking lot, but it led Marix will always display information in accordance with a state park number of parking locations. Keywords: Parking, Technology, Safety, Comfort, information